×
Language:

Assignment 4 — Solutions 2/6/04
Problem 3.1
We have azimuthal symmetry and charge-free space so expand in Legendre polynomials as in eq. 3.33:
F
H
,
L
=
l
=
0
A
A
l

l
+
B
l

-
H
l
+
1
L
E

P
l
H
cos
L
F
§
=
a
=
Q
J
pÅÅÅÅÅ
2
-
N
F
§
=
b
=
Q
J
q-pÅÅÅÅÅ
2
N
ϖ
z
ab
where
Q
is the step function. Use the orthogonality condition eq 3.21 to integrate both sides multiplied by
P
H
cos
L
:
l
=
0
A
A
l

a
l
+
B
l

a
-
H
l
+
1
L
E

‡
-
11

H
cos
L
P
l
H
cos
L

P
H
cos
L
=
‡
-
11

H
cos
L
Q
J
pÅÅÅÅÅ
2
-
N

P
H
cos
L
l
=
0
A
A
l

a
l
+
B
l

a
-
H
l
+
1
L
E

2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2

+
1
d
kl
=

‡
01

H
cos
L
P
H
cos
L
A

a
+
B

a
-
H
+
1
L
=
ÅÅÅÅÅÅÅ
2
H
2

+
1
L

‡
01

H
cos
L
P
H
cos
L
The integral is done in Jackson 3.26 for odd
. For even
the
P
H
x
L
x
=
0, so we may double theintegration range and take half of the result; also we gratuitously multiply by
P
0
H
x
L
=
1:
‡
01

H
cos
L
P
H
cos
L
=
1
ÅÅÅÅÅ
2

‡
-
11

H
cos
L
P
H
cos
L

P
0
H
cos
L
=
1
ÅÅÅÅÅ
2

2
d
0
A

a
+
B

a
-
H
+
1
L
=
ÅÅÅÅÅÅÅ
2

loooomnoooo
d
0
,
even
ikjjj
-
1
ÅÅÅÅÅ
2
y{zzz
H
-
1
2

H
2

+
1
L

H
-
2
L
!!ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2
@H
+
1
Lê
2
D
!
,
odd
The same procedure works for the
=
b
boundary condition except we're now integrating over
-
1
§
cos
q§
0 on theright-hand-side, which can be evaluated by a change of integration variables cos
qØ-
cos
and noting that
P
H
-
x
L
=
H
-
1
L

P
H
x
L
(this is just a statement of the odd/evenness of the function):1

A

b
+
B

b
-
H
+
1
L
=
ÅÅÅÅÅÅÅ
2
H
2

+
1
L

‡
-
10

H
cos
L
P
H
cos
L
=-
ÅÅÅÅÅÅÅ
2
H
2

+
1
L

‡
10

H
cos
L
P
H
-
cos
L
=
H
-
1
L

ÅÅÅÅÅÅÅ
2
H
2

+
1
L

‡
01

H
cos
L
P
H
cos
L
=
H
-
1
L

ÅÅÅÅÅÅÅ
2

loooomnoooo
d
0
,
even
ikjjj
-
1
ÅÅÅÅÅ
2
y{zzz
H
-
1
2

H
2

+
1
L

H
-
2
L
!!ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2
@H
+
1
L ê
2
D
!
,
odd
Define
ª
ÅÅÅÅÅÅÅ
2

loooomnoooo
d
0
,
even
ikjjj
-
1
ÅÅÅÅÅ
2
y{zzz
H
-
1
2

H
2

+
1
L

H
-
2
L
!!ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2
@H
+
1
L ê
2
D
!
,
odd
A

a
+
B

a
-
H
+
1
L
=
ó
A
+
B

a
-
H
2

+
1
L
=

a
-
ó
A

a
2

+
1
+
B
=

a
+
1
A

b
+
B

b
-
H
+
1
L
=
H
-
1
L

ó
A
+
B

b
-
H
2

+
1
L
=
H
-
1
L

b
-
ó
A

b
2

+
1
+
B
=
H
-
1
L

b
+
1
Subtract the second row from the first to solve for
A
and
B
:
A
l
=
a
l
+
1
-
H
-
1
L
l

b
l
+
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
a
2

l
+
1
-
b
2

l
+
1

l
,
B
l
=
a
-
l
-
H
-
1
L
l

b
-
l
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
a
-
H
2

l
+
1
L
-
b
-
H
2

l
+
1
L

l
F
H
,
L
=
ÅÅÅÅÅÅÅ
2
+
l
=
1
A
A
l

l
+
B
l

-
H
l
+
1
L
E

P
l
H
cos
L
I've separated out the
A
0
=
a
-
b
ÅÅÅÅÅÅÅÅÅÅÅÅ
a
-
b

0
=
ÅÅÅÅÅÅ
2
and
B
0
=
0 pieces to facilitate taking limits, which we will do next. For
b
Ø
this is like having no outer sphere and being outside a northern hemisphere at potential
, i.e. half of the
a
ê
version of eq. 3.36 superimposed with a constant potential
+
.
l
is independent of
a
and
b
, so we just need to worryabout the limiting forms of
A
l
and
B
l
(keeping in mind that
l
¥
0 so apparently positive powers really are such):
lim
b
Ø¶
A
l
=
lim
b
Ø¶
a
l
+
1
ê
b
l
+
1
-
H
-
1
L
l
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
a
2

l
+
1
ê
b
l
+
1
-
b
l

l
=
lim
b
Ø¶
0
-
H
-
1
L
l
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
0
-
b
l

l
=
0,
l
0lim
b
Ø¶
B
l
=
lim
b
Ø¶
a
-
l
-
H
-
1
L
l
ê
b
l
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
a
-
H
2

l
+
1
L
-
1
ê
b
2

l
+
1

l
=
a
-
l
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
a
-
H
2

l
+
1
L

l
=
a
l
+
1

l
The first few (nonzero,
l
>
0)
l
's are
1
=
3
ê
2

H
ê
2
L
,
3
=-
7
ê
8

H
ê
2
L
,
5
=
11
ê
16

H
ê
2
L
, so
lim
b
Ø¶
F
H
,
L
=
l
=
0
l
J
a
ÅÅÅÅÅ
N
l
+
1

P
l
H
cos
L
=
ÅÅÅÅÅÅÅ
2
ÄÇÅÅÅÅÅÅÅÅ
1
+
3
ÅÅÅÅÅ
2

J
a
ÅÅÅÅÅ
N
2

P
1
H
cos
L
-
7
ÅÅÅÅÅ
8

J
a
ÅÅÅÅÅ
N
4

P
3
H
cos
L
+
11
ÅÅÅÅÅÅÅÅÅ
16

J
a
ÅÅÅÅÅ
N
6

P
5
H
cos
L
+
ÉÖÑÑÑÑÑÑÑÑ
a
Ø
0 this is like having no inner sphere and being inside a southern hemisphere at potential
, which is half of the
ê
a
version of eq. 3.36 superimposed with
-
and with the substitution
Ø-
after that:2

lim
a
Ø
0
A
l
=
0
-
H
-
1
L
l

b
l
+
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
0
-
b
2

l
+
1

l
=
ikjjj
-
1
ÅÅÅÅÅ
b
y{zzz
l

l
lim
a
Ø
0
B
l
=
lim
a
Ø
0
a
l
+
1
-
a
2

l
+
1
H
-
1
L
l

b
-
l
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
1
-
a
2

l
+
1

b
-
H
2

l
+
1
L

l
=
0lim
a
Ø
0
F
H
,
L
=
l
=
0
l
J
-
ÅÅÅÅÅ
b
N
l

P
l
H
cos
L
=
ÅÅÅÅÅÅÅ
2
ÄÇÅÅÅÅÅÅÅÅ
1
-
3
ÅÅÅÅÅ
2
ÅÅÅÅÅ
b

P
1
H
cos
L
+
7
ÅÅÅÅÅ
8
J
ÅÅÅÅÅ
b
N
3

P
3
H
cos
L
-
11
ÅÅÅÅÅÅÅÅÅ
16
J
ÅÅÅÅÅ
b
N
5

P
5
H
cos
LÉÖÑÑÑÑÑÑÑÑ
Problem 3.3
F
§
q=p
ê
2,
<
R
=
=
constant
s
H
v
L
=s
0
I
R
2
-v
2
M
-
1
ê
2
ˆ
x
ϖϖ
=
2 2
x x z
ϖ
= +
ˆ
x zz
=
x y z R
σ
To find the coefficients we use the trick of calculating the potential at an arbitrary point
z
>
R
on the
z
-axis:
F
H
z

z
`
L
=
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
pe
0

‡

3
x
£
r
H
x
÷
£
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
x
÷
-
x
÷
£
§
=
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
pe
0

‡
02
p
v
£

f
‡
0
R

v
£
s
0
H
R
2
-v
£
2
L
-
1
ê
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
H
z
2
+v
£
2
L
1
ê
2
=s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
2
e
0

‡
0
R

v
£
v
£
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
è!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
R
2
z
2
+
H
R
2
-
z
2
L H
v
£
L
2
-
H
v
£
L
4
ì
change variable
u
ª v
£
2
=s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
e
0

‡
0
R
2

u
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
è!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
R
2
z
2
+
H
R
2
-
z
2
L
u
-
u
2
=s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
e
0
ÄÇÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
-
sin
-
1
-
2
u
+
H
R
2
-
z
2
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
"#########################################H
R
2
-
z
2
L
2
+
4
R
2
z
2
ÉÖÑÑÑÑÑÑÑÑÑÑÑÑÑÑ
0
R
2
=s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
e
0
ÄÇÅÅÅÅÅÅÅÅÅÅ
-
sin
-
1
-
2
u
+
R
2
-
z
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
R
2
+
z
2
ÉÖÑÑÑÑÑÑÑÑÑÑ
0
R
2
=s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
e
0

ikjjjjj
sin
-
1

R
2
-
z
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
R
2
+
z
2
-
sin
-
1
-
2
R
2
+
R
2
-
z
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
R
2
+
z
2
y{zzzzz
=s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
e
0

ikjjjjj
sinh
-
1
ikjjjjj
Â
R
2
-
z
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
R
2
+
z
2
y{zzzzz
-
sin
-
1
H
-
1
Ly{zzzzz
=s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
e
0

ikjjjjjjjjjjj
ln
ikjjjjjjjjjjj
Â
R
2
-
z
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
R
2
+
z
2
+
&''''''''''''''''''''''''''''''''''' ikjjjj
Â
R
2
-
z
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
R
2
+
z
2
y{zzzz
2
+
1
y{zzzzzzzzzzz
+pÅÅÅÅÅ
2
y{zzzzzzzzzzz
=s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
e
0
ÄÇÅÅÅÅÅÅÅÅÅÅ
pÅÅÅÅÅ
2
-Â
ln
ikjjjjj
Â
R
2
-
z
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
R
2
+
z
2
+
2

Rz
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
R
2
+
z
2
y{zzzzzÉÖÑÑÑÑÑÑÑÑÑÑ
=s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
e
0

ikjj
pÅÅÅÅÅ
2
-Â
ln
Â
R
+
z
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
R
+Â
z
y{zz
ì
ln
H
L
= -Âp
ê
2
= -s
0
ÅÅÅÅÅÅÅÅÅÅÅÅÅ
4
e
0
Â
ln
Â
z
-
R
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÂ
z
+
R
Since the disk is at
z
=
0 has constant potential
,
F
H
0
L
=
= ps
0
ê
4
e
0
so
s
0
=
4
e
0

ê
p
. Now to the cases:(a)For
>
R
, let
u
ª
R
ê
z
so 0
§
u
§
1 and we can expand about
u
=
0 using ln

1
+e
ÅÅÅÅÅÅÅÅÅÅÅ
1
-e
=
2

n
=
0
e
2

n
+
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2

n
+
1
:3
Search History:
Searching...
Result 00 of 00
00 results for result for
• p.

Notes